All that glitters is not gold: prevalence and relevance of psychotic‐like experiences in clinical sample of children and adolescents aged 8–17 years old. Issue 4 (31st August 2016) - Pontillo, Maria; De Luca, Maria; Pucciarini, Maria Laura; Vicari, Stefano; Armando, Marco
Abstract: Aim: Recent studies have examined the prevalence of psychotic‐like experiences (PLEs) and their relationship with functioning, psychopathology and distress in adult and mixed young adult and adolescent samples. There is, however, a lack of knowledge about the prevalence and clinical weight of PLEs in clinical child and adolescent (CAD) populations. Available research has primarily been conducted on community populations, and even clinical samples mostly used self‐reported questionnaires. These studies also recruited participants 12 years old and older, with a consequent lack of information on children from 8 to 11 years old. We examined the prevalence of PLEs and their relationship with psychiatric diagnosis, functioning, intelligence quotient (IQ), anxiety and depressive symptoms in a clinical sample aged 8–17 years old. Methods: The study was conducted on a clinical sample of 46 CAD with PLEs compared to a clinical sample of 60 CAD without PLEs. The two groups were compared on global, social and role functioning, IQ, anxiety and depressive symptoms, and number of psychiatric diagnoses. Results: Global, role and social functioning were significantly lower in the CAD clinical sample with PLEs. These significant differences were maintained when the covariate IQ, number of psychiatric diagnoses or level of anxiety or depression was added. No significant age‐related differences in the presence of PLEs were found. Conclusion: The findings of this study show that PLEs are common in a clinical sample of CAD, even those under 12 years old. The presence of PLEs should therefore be investigated and considered in planning treatment of non‐psychotic psychiatric disorders in CAD.